Changes in Morphology, Metabolism and Composition of Cuticular Wax in Zucchini Fruit During Postharvest Cold Storage - Carvajal, Fátima; Castro-Cegrí, Alejandro; Jiménez-Muñoz, Raquel; Jamilena, Manuel; Garrido, Dolores; Palma, Francisco (Frontiers in Plant Science, 2021)
Cuticle composition is an important economic trait in agriculture, as it is the first protective barrier of the plant against environmental conditions. The main goal of this work was to study the role of the cuticular wax in maintaining the postharvest quality of zucchini fruit, by comparing two commercial varieties with contrasting behavior against low temperatures; the cold-tolerant variety ‘Natura’, and the cold-sensitive ‘Sinatra’, as well as ‘Sinatra’ fruit with induced-chilling tolerance through a preconditioning treatment (15 ºC for 48h). The freshly-harvested ‘Natura’ fruit had a well-detectable cuticle with a significant lower permeability and a subset of 15 up-regulated cuticle-related genes. SEM showed that zucchini epicuticular waxes mainly consisted in round-shaped crystals and clusters of them, and areas with more dense crystal deposition were found in fruit of ‘Natura’ and of preconditioned ‘Sinatra’. The epicuticular wax load per surface was higher in ‘Natura’ than in ‘Sinatra’ fruit at harvest and after 14 days at 4 ºC. In addition, total epicuticular wax load only increased in ‘Natura’ and preconditioned ‘Sinatra’ fruit with cold storage. With respect to the chemical composition of the waxes, the most abundant components were alkanes, in both ‘Natura’ and ‘Sinatra’, with similar values at harvest. The total alkane content only increased in ‘Natura’ fruit and in the preconditioned ‘Sinatra’ fruit after cold storage, whereas the amount of total acids decreased, with the lowest values observed in the fruit that showed less chilling injury (CI) and weight loss. Two esters were detected, and their content also decreased with the storage in both varieties, with a greater reduction observed in the cold-tolerant variety in response to low temperature. Gene expression analysis showed significant differences between varieties, especially in CpCER1-like and CpCER3-like genes, involved in alkane production, as well as in the transcription factors CpWIN1-like and CpFUL1-like, associated with cuticle development and epidermal wax accumulation in other species. These results suggest an important role of the alkane biosynthetic pathway and cuticle morphology in maintaining the postharvest quality of zucchini fruit during the storage at low temperatures.